2014
DOI: 10.1523/jneurosci.2075-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic Cell-Specific Synaptotagmins inDrosophila: Localization to Dense-Core Granules and Regulation by the bHLH Protein DIMMED

Abstract: Bioactive peptides are packaged in large dense-core secretory vesicles, which mediate regulated secretion by exocytosis. In a variety of tissues, the regulated release of neurotransmitters and hormones is dependent on calcium levels and controlled by vesicle-associated synaptotagmin (SYT) proteins. Drosophila express seven SYT isoforms, of which two (SYT-␣ and SYT-␤) were previously found to be enriched in neuroendocrine cells. Here we show that SYT-␣ and SYT-␤ tissue expression patterns are similar, though no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…The molecular machinery for DCV fusion is still being elucidated, but is thought to have some overlap with SV pathways. For example, SNAREs are thought to be required, as well as additional members of the Synaptotagmin family, including Syta and Sytb (Adolfsen et al 2004;Park et al 2014). In addition, one wellcharacterized DCV-specific regulator of release has been identified-the Ca 2+ -activated protein for secretion (CAPS).…”
Section: Dense Core Vesicle Releasementioning
confidence: 99%
See 1 more Smart Citation
“…The molecular machinery for DCV fusion is still being elucidated, but is thought to have some overlap with SV pathways. For example, SNAREs are thought to be required, as well as additional members of the Synaptotagmin family, including Syta and Sytb (Adolfsen et al 2004;Park et al 2014). In addition, one wellcharacterized DCV-specific regulator of release has been identified-the Ca 2+ -activated protein for secretion (CAPS).…”
Section: Dense Core Vesicle Releasementioning
confidence: 99%
“…This transgenic line has proved highly valuable for DCV biology, revealing mechanisms of activity-dependent recruitment of DCVs (Shakiryanova et al 2005), DCV capture at active terminals (Wong et al 2012;Bulgari et al 2014), presynaptic ER-dependent Ca 2+ release driving DCV fusion (Shakiryanova et al 2007(Shakiryanova et al , 2011, and partial depletion of DCV contents upon release (Wong et al 2015). In addition to aspects of DCV release and trafficking, studies have revealed the role of the basic helix-loop-helix transcription factor Dimmed in driving neuroendocrine cell fate, including its role in regulating the expression of specific DCV proteins (Hewes et al 2006;Hamanaka et al 2010;Park et al 2011Park et al , 2014. Although the identification of the mechanisms that control DCV trafficking and fusion have lagged behind those of SV release (largely due to the ease in physiologically measuring the consequences of SV fusion), new tools in the DCV field are beginning to fill in many of the missing gaps in DCV biology.…”
Section: Dense Core Vesicle Releasementioning
confidence: 99%
“…5, Extended Data Fig. 5) [24][25][26] . This is in line with previous reports of neurosecretory cells populating the dorsomedian larval brain 22 , and with ultrastructural observations, which show that cells in the dorsomedian Platynereis brain are rich in dense core vesicles while synapses are often sparse or absent 27 .…”
Section: The Apical Nervous Systemmentioning
confidence: 99%
“…In these cases, neuronal manipulation will likely affect the release of both biogenic amines/neuropeptides and classical transmitters. On the other hand, there is also evidence for differences between the molecular release mechanisms of amine/peptide-containing dense core vesicles and small transmitter-containing synaptic vesicles (e.g., Renden et al 2001;Park et al 2014), and biogenic amine and neuropeptide release may not be restricted to active synaptic zones (e.g., Karsai et al 2013). This may explain the inefficiency of TNTE in OA/TA neurons (Sweeney et al 1995).…”
Section: Benefits and Drawbacks Of Effector Gene Use In Larval Drosopmentioning
confidence: 99%